The Effect of Shopee Express Drop Point Service Quality on Customer Satisfaction and Loyalty with Partial Least Square Structural Equation Model - Gloria Margareth Hutagalung; Eko Pujianto; Retno Wulan Damayanti (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2023)
Abstract— The existence of the internet provides significant changes in people's lives, one of which is shopping activities. In 2023, Shopee occupies the first position with the most number of visitors. Shopee has a shipping service, namely Shopee Express Drop Point. Complaints from customers have been increasingly volatile, causing a decline in the company's reputation. This research needs to be conducted to find out the dimensions that significantly influence customer satisfaction and loyalty and to provide improvement guidelines for the company. The research was conducted quantitatively using a questionnaire with a sample of 223 respondents. Sampling was done using a random sampling technique. The tools used in processing the data are PLS-SEM. The results of this study are the dimensions of reliability, responsiveness, accessibility, security, and empathy that have a significant positive effect on customer satisfaction at Shopee Express Drop Point, while customer loyalty is influenced by the dimensions of accessibility, security, and empathy. The results of this study were correlated with suggestions from respondents and review on Google Reviews to obtain a repair guide for the Shopee Express Drop Point company.